Proposals for Development for Annual Plan 1968-69 Government of Gujarat - Planning Commission (Planning Commission, 1968)
The distribution of the amount of Rs. 400 lakhs among Minor Irrigation, Rural Electrification, Roads and Water Supply is purely tentative and is subject to change. The targets contemplated in the proposals contained within the size of Rs. 85.18 crores do not take into account the above mentioned additional outlay of Rs. 4.50 crores.
Government of Gujarat, General Administration Department (Planning)